PENGUNGKAPAN LAPORAN KEUANGAN KONSOLIDASI BERDASARKAN PSAK 4 (REVISI 2009) PADA PT BCA - Saputro, Widyan Ade; Rabbani, Yusuf Thoriq; Panggiarti, Endang Kartini (ISAS, 2023)
This research aims to determine the requirements for disclosing consolidated financial statements based on PSAK 4 (Revised 2009) at PT. Bank Central Asia Tbk. The methods used in this research are descriptive analysis. The secondary data consists of the Consolidated Financial Statements of PT. Bank Central Asia Tbk as of December 31, 2021, and 2022. The results of the research indicate that: (1) the consolidated statement of financial position; (2) the consolidated statement of comprehensive income; (3) the consolidated statement of changes in equity; and (4) the consolidated statement of cash flows of PT. Bank Central Asia Tbk and its Subsidiaries are in accordance with PSAK 4 (Revised 2009). The Parent Entity, in consolidating the financial statements of its Shariah-based subsidiaries, refers to Shariah PSAK and the Guidelines for Shariah Banking Accounting in Indonesia (PAPSI). The hypothesis in this research is accepted. Kata kunci: PSAK 4, Consolidated Financial Reports.